Postoperative Cerebral Oxygen Saturation in Children After Congenital Cardiac Surgery and Long-Term Total Intelligence Quotient: A Prospective Observational Study. Issue 6 (12th February 2021) - Carra, Giorgia; Flechet, Marine; Jacobs, An; Verstraete, Sören; Vlasselaers, Dirk; Desmet, Lars; Van Cleemput, Hanna; Wouters, Pieter; Vanhorebeek, Ilse; Van den Berghe, Greet; Güiza, Fabian; Meyfroidt, Geert
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: During the early postoperative period, children with congenital heart disease can suffer from inadequate cerebral perfusion, with possible long-term neurocognitive consequences. Cerebral tissue oxygen saturation can be monitored noninvasively with near-infrared spectroscopy. In this prospective study, we hypothesized that reduced cerebral tissue oxygen saturation and increased intensity and duration of desaturation (defined as cerebral tissue oxygen saturation < 65%) during the early postoperative period, independently increase the probability of reduced total intelligence quotient, 2 years after admission to a PICU. DESIGN: Single-center, prospective study, performed between 2012 and 2015. SETTING: The PICU of the University Hospitals Leuven, Belgium. PATIENTS: The study included pediatric patients after surgery for congenital heart disease admitted to the PICU. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Postoperative cerebral perfusion was characterized with the mean cerebral tissue oxygen saturation and dose of desaturation of the first 12 and 24 hours of cerebral tissue oxygen saturation monitoring. The independent association of postoperative mean cerebral tissue oxygen saturation and dose of desaturation with total intelligence quotient at 2-year follow-up was evaluated with a Bayesian linear regression model adjusted for known confounders. According to a noninformative prior, reduced mean cerebral tissue oxygen saturation during the first 12 hours of monitoring results in a loss of intelligence quotient points at 2 years, with a 90% probability (posterior β estimates [80% credible interval], 0.23 [0.04–0.41]). Similarly, increased dose of cerebral tissue oxygen saturation desaturation would result in a loss of intelligence quotient points at 2 years with a 90% probability (posterior β estimates [80% credible interval], –0.009 [–0.016 to –0.001]). CONCLUSIONS: Increased dose of cerebral tissue oxygen saturation desaturation and reduced mean cerebral tissue oxygen saturation during the early postoperative period independently increase the probability of having a lower total intelligence quotient, 2 years after PICU admission.